The Teaching Method of Science Subject in Primary Schools Based on Students’ Competency Development: Results From a Field Study - Van, Hong Bui; Doan, Thi Ngan (Asian Journal of Interdisciplinary Research, 2021)
Renovating the General Education Curriculum is one of the most important goals of the education renovation in Vietnam at the present. Particularly, the renovation of teaching methods has been receiving increasing attention during the past few years. This originates from the growing demands for social developments and the inadequacies of the current General Education curriculum. This article explores the current teaching methods used to teach the science subject with an orientation toward the development of students’ competencies in primary schools in Ho Chi Minh City, Vietnam. This scientific and objective account will provide the foundation for improving teaching methods, enhancing the quality of science education in primary schools with an orientation toward students’ competency development to meet the demands for the renovation of the General Education Curriculum at the primary level.